Tipologija slovenskih jezika: Prikaz / Book Review - Henzelmann, Martin (Journal of the Faculty of Philosophy in Sarajevo / Radovi Filozofskog fakulteta u Sarajevu, ISSN 2303-6990 on-line, 2023)
Book review: Манучарян, Иветта, 2021. Типология славянских языков. Ереван: Издательство ЕГУ, 368 с.